2021
DOI: 10.1002/slct.202101259
|View full text |Cite
|
Sign up to set email alerts
|

Amidation and Intramolecular Aza‐Michael Reaction: One‐Pot Synthetic Strategy of Isoindolinones

Abstract: Herein, we report one-pot Cu(I) catalyzed open flask synthetic strategy of 3-substituted N-pyridinyl isoindolinones from alkyl (E)-3-(2-formylphenyl)acrylate by oxidative amidation and intramolecular aza-Michael reaction using cheap air stable Cu(I) single catalyst. We have also established a synthetic route of Naryl substituted isoindolinones with acid-amine coupling reaction of (E)-2-(3-alkoxy-3-oxoprop-1-en-1-yl)benzoic acid followed by aza-Michael reactions. Unexpected synthetic route of N-(1H-inden-1-yl)p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The lower activation energy observed by the Kissinger method than the theoretically predicted value is due to the catalytic action of Cu 2 I 2 and also the simultaneous cross-linking reaction of TMPTA with TETA. The catalysis of aza-Michael reactions using cuprous halide was reported by Kantam et al and Kang et al separately. , The promising catalytic activity of CuI for aza-Micahel addition was reported by Asraf Ali et al, and a plausible mechanism was also suggested. , …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The lower activation energy observed by the Kissinger method than the theoretically predicted value is due to the catalytic action of Cu 2 I 2 and also the simultaneous cross-linking reaction of TMPTA with TETA. The catalysis of aza-Michael reactions using cuprous halide was reported by Kantam et al and Kang et al separately. , The promising catalytic activity of CuI for aza-Micahel addition was reported by Asraf Ali et al, and a plausible mechanism was also suggested. , …”
Section: Resultsmentioning
confidence: 96%
“…32,33 The promising catalytic activity of CuI for aza-Micahel addition was reported by Asraf Ali et al, and a plausible mechanism was also suggested. 34,35 2.2.4. Morphology Studies.…”
Section: Molecular Modeling Studiesmentioning
confidence: 99%
“…5. [22][23][24][25][26] Additionally, in medicinal chemistry aspects to involve a scaffold in the development of drugs, the scope of expansion of huge chemical space is also important. The interesting huge chemical space of aristolactams can be facilitated by new derivative chemical space expansion (NDCSE) (Fig.…”
Section: Ashutosh Deymentioning
confidence: 99%
“…Hence, the construction of these potentially valuable scaffolds has received considerable attention resulting in the development of several synthetic strategies . Although, numerous synthetic methods were reported, most of those efforts rely on harsh reaction conditions, toxic, expensive transition metal complexes/ligands, the prerequisite installation of directing groups, the amide starting material, the use of stoichiometric amounts of additives/oxidants, and a limited substrate scope (Scheme a). , To the best of our knowledge, there are very few reports available for the synthesis of isoindolinone acetate motifs using organocatalysis. Michon and co-workers reported a phase transfer-catalyzed intramolecular aza-Michael addition for the synthesis of isoindolinone acetates using ortho -alkenyl substituted benzamides (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%